Microsoft Exchange Server 2003 - Redmond, Tony (Digital Press, 2011)
Providing thorough coverage of implementation, migration and management issues for Exchange 2000 and 2003, this book also describes the best practices of one of the largest Exchange consulting groups outside Microsoft.